PENGARUH PERLAKUAN KADAR AIR PADA BUAH KETUMBAR DAN ASPEK BIOLOGI Stegobium paniceum (L) (Coleoptera : Anobiidae) - Hazen Arrazie Kurniawan; Imam Hartono Bangun; Nurhajijah Nurhajijah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
The use of coriander seeds as acooking spice in a number of food processing is widely found and damage to coriander is known to be cause by Stegobium paneceum (L), which cause a decrease in a decreased fruid weigth, an unattractive fruit shape, and a musty smell, which is a form of decreased fruit weight, qulity and quantity of coriander seeds. Based on the observation of the biological aspect, the egg phase is 6-12 days, larvae is 10-140 days, pupa is 7-12 days, and 25-37 days. In the treatment of differences in water content to coriander, the mortality value of Z1 was 16,2%, Z2was 12,6%, Z3 was 5%, and Z4 was 1% at 30 day after observation. The shrinkage that occurred in coiander seeds was 0,14% (Z4), 0,04% (Z3), 0,02% (Z2), and 0,02% (Z1).